Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Terhadap Kinerja Pegawai Pada Badan Pengelolaa Keuangan dan Pendapatan Daerah Kabupaten Pamekasan Yang Di Mediasi Oleh Motivasi - Sri Mulyani; Nugroho Mardi; Agus Setiawan (Universitas 45 Surabaya, 2024)
This article reviews the Influence of Leadership Style, Work Environment, on Employee Performance with Motivation as an Intervening Variable. Where the influence of employee performance on motivation as a mediating variable includes leadership style, work environment, so in this article the author will review two variables that have a role or influence on employee performance with motivation as a mediating variable. The implementation of this literature review article is as follows: 1) leadership style influences employee performance; 2) leadership style influences motivation; 3) work environment affects motivation; 4) work environment influences employee performance; 5) motivation influences employee performance; 6) leadership style not influence employee performance mediated motivation; 7) work environment not influence employee performance mediated motivation.